New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene) - Alekseev, Vitalii I.; Bukejs, Andris (Zootaxa, 2016)
The fossil silvanid beetle Mistran ot gen. et sp. nov. is described from Baltic amber. The new taxon is illustrated and compared with morphologically close extant and fossil taxa. A checklist of fossil Silvanidae is provided.